Inexpensive Amorphous FeIII Oxo‐/Hydroxide as Highly Active and Ultradurable Electrocatalyst for Water Electrolysis. Issue 5 (1st March 2021) - Mathi, Selvam; Jayabharathi, Jayaraman
Abstract: Developing highly active, cost‐effective, and robust electrocatalysts for the oxygen evolution reaction (OER) still remains a crucial challenge for enhancing the conversion of sustainable energy resources. The performances of existing electrocatalysts is restricted by low electronic conductivity and the limited amount of active sites. Herein, newly synthesized Fe III OH nanoparticles (NPs) are shown to be efficient and durable electrocatalysts for the OER reaction. Fe III OH NP‐coated nickel foam (Fe III OH NPs/NF) operates at an overpotential of 300 mV (@10 mA cm −2 ) with excellent stability even after 30 h and shows higher stability relative to a cell voltage of 1.55 V in alkaline media, which is substantially lower than the commercial electrocatalyst IrO2 (1.61 V). The Fe III OH NPs/NF overpotential of 300 mV at 10 mA cm −2 is 89 and 127 mV lower than IrO2 /NF (389 mV) and NF (427 mV), respectively. The Tafel slope of Fe III OH NPs/NF (104 mV dec −1 ) is lower than IrO2 /NF (164 mV dec −1 ) and NF (199 mV dec −1 ). The calculated turnover frequency (TOF) of Fe III OH NPs (0.0128 s −1 ) is approximately five times higher than that of the IrO2 catalyst (0.0089 s −1 ) at 1.60 V. This reflects that the Fe III OH NP catalyst is intrinsically active, giving outstanding OER performances and showing satisfactory kinetics to overcome the sluggish water oxidation rate. Solar water electrolysis shows continuous evolution of oxygen and hydrogen gas at the anode and cathode, respectively, at 1.55 V. The amount of hydrogen generated during solar water electrolysis was calculated as 3.22 mmol h −1  cm −2, which is close to the coulombic efficiency at 1.55 V. This demonstration develops the hope for superior exploration of Fe III OH NPs/NF toward the expansion of real and large‐scale hydrogen production with the lowest price. Abstract : Ready to evolve : Fe III OH nanoparticles (NPs) are reported as an efficient oxygen evolution reaction (OER) electrocatalyst for water splitting in alkaline media. The Fe III OH NPs‐coated nickel foam electrocatalyst requires an overpotential of 300 mV (10 mA cm −2 ) and exhibits excellent electrode stability even after 30 h. Solar water electrolysis is also carried out with continuous evolution of oxygen and hydrogen gas on the anode and cathode, respectively, at 1.55 V.